Foodies and food tourism - Getz, Donald; Andersson, Tommy; Vujicic, Sanja (Goodfellow Publishers, 2014)
Foodies and Food Tourism supplies comprehensive new evidence and theory based overview of the phenomenon of food tourism and how it is being, or should be developed and marketed and understood.